Biosynthetic alginate–polyester hydrogels with inherent free radical scavenging activity promote cellular response. (November 2013) - Thankam, Finosh G; Muthu, Jayabalan
The prevention of deleterious effects of reactive oxygen species on the cell growth by biosynthetic hydrogels based on alginate–polyester copolymer was studied using H2 O2 as the model ROS molecule. Chemically cross-linked biosynthetic hydrogels of alginate- co -poly(propylene fumarate)–n-butyl methacrylate, alginate- co -poly(propylene fumarate)–methyl methacrylate, alginate- co -poly(propylene fumarate)–2-hydroxyethyl methacrylate, and alginate- co -poly(propylene fumarate)– N, N ′-methylene bisacrylamide with different biostabilities were prepared. We found that they were able to resist reactive oxygen species penetration into the cell to a greater extent which was evident from the live/dead assay, and increased intracellular glutathione levels compared to the H2 O2 -treated control. The hydrogels maintained the genomic integrity which was confirmed by comet assay. The inherent protective effects of these hydrogels without any antioxidant moiety may be mediated by dual mechanism: (a) prevention of migration of H2 O2 into the cells by calcium-induced conformational changes and rigidity in phospholipids present in the surface membrane of cells by the calcium generated from degradation of hydrogel and (b) by the dilution of H2 O2 by the free water in the hydrogel. These hydrogels have potential as injectable hydrogels to manage myocardial infarction and ischemia.